(3Gdabg GdQVhjs - (3CHh GdMSf, GdQVi, Ydj GdQVi, Ydj Hf ehSi GdcGXe Hf LYaQ GdUGOb, J (B203(3gs ((3EjQGgje Hf CMeOs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3Ef Chd eG GaJQV Gddg Ydi YHGOg hChLH Ydi Ndbg eYQaI GdhMOGfjI bGd Gddg JHGQc hJYGdi heG bOQhG Gddg Mb eYQaJg hJQhi Yf HYV GdYdeGA Ydjge GdSdGe Cfg bGd aj JaSjQ gPg GdBjI(B...s
(3BNQgG (B:s
... (3HGH EPG GSJbHdJ GdbHdI aj UdGI GdRhGd (B...(3hge efc ZjQ eMJLHjf JQi hdG JQi aj GdedC GdCYdi JSeY hJQi eG jNai hGNai aJHGQc hJYGdjJ YeG jbhdhfs
(3efShNI ef fSNI HNW GdeDdas
(3JHUQI GdYfhGf (B:s
(3GdefShH ddQVi Chd ef PcQg GdeLdSj aj HMGQ GdCfhGQ , hfai fSHJg GdMQ GdYGedj aj Ced GdBed (B2: 364s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 \26s
(3GdPQjYI (B16 - 207 (1283)s
Keywords: (3GdJhMjO hGdedd hGdfMds